2014
DOI: 10.2478/folmed-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Of Lamps And Ykl-40 Tissue Expression In Glial Tumors

Abstract: INTRODUCTION: YKL-40 is a glycoprotein believed potentially to be a marker of various pathological processes. High levels of YKL-40 have been found in cancer and chronic infl ammatory diseases. The function of the glycoprotein is not completely known yet. A possible involvement in angiogenesis and tumor aggressiveness is supposed. Lysosome-associated membrane glycoproteins (LAMP) 1 and 2 are highly conserved proteins with still undefi ned biological functions. There is evidence that they are implicated in auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…However, IHC reaction did not correlate with any of the clinical parameters, which is in accordance with other reports (22). To the best of our knowledge this is the first study on the expression of YKL-40 in non-melanoma skin cancers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, IHC reaction did not correlate with any of the clinical parameters, which is in accordance with other reports (22). To the best of our knowledge this is the first study on the expression of YKL-40 in non-melanoma skin cancers.…”
Section: Discussionsupporting
confidence: 91%
“…The studies available so far have clearly shown that many other malignant cells or cell lines express and release this protein. Positive YKL-40 expression has been reported in breast, colon, lung, prostate, thyroid, ovarian, hepatocellular, and renal cancers, as well as in glial and chondroid tumors, melanoma, osteosarcoma and soft tissue sarcomas (14,(19)(20)(21)(22)(26)(27)(28)(29)(30). It was also found that squamous cell carcinomas developed within the mucous membranes of larynx, pharynx, oral cavity and esophagus show YKL-40 expression (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed YKL40 to be highly expressed in tumor cells, consistent with previous reports [ 36 , 37 , 38 ]. Inflammatory cells also showed some expression of YKL40, which has been previously attributed to the presence of tumor-infiltrating macrophages [ 22 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our evaluation of YKL40, 28 out of 55 (50.9%) samples had a low percentage of positive YKL40 tumor cells (<25%), while 12 out of 55 (21.8%) had a high percentage (>75%) ( Table 4 ). The majority of YKL40 expression (70.9%) was observed to be strong (and cytoplasmatic) ( Figure 1 g,h), as has been previously reported [ 36 , 37 , 38 ]. Moreover, YKL40 expression was observed, albeit to a lesser extent, in inflammatory cells.…”
Section: Resultssupporting
confidence: 85%